Selection of source material and agricultural practices for cowpea cultivation in order to ensure uninterrupted production of vegetables for food processing enterprises - M. O. Burlyaeva; M. V. Gurkina; E. A. Krylova; Yu. V. Ukhatova (Труды по прикладной ботанике, генетике и селекции)
Background. Vigna unguiculata (L.) Walp. is an important legume crop, widely cultivated in countries with subtropical and tropical climates. Vegetable pods of this species are highly nutritious and used as food similarly to vegetable cultivars of common bean. The crop is resistant to high temperatures, undemanding to soil fertility, and successfully grown in the southern regions of Russia. In order to expand the cultivation areas and increase the profitability of crop production, it is necessary to select agricultural practices and cultivars that would enable crop producers to supply food processing enterprises with vegetable products during a longer period of time.Materials and methods. Vegetable accessions of cowpea from the VIR collection were studied at Astrakhan Experiment Station of VIR in 2021–2023. Accessions with various durations of the growing season were analyzed after springtime sowing. Earlymaturing cultivars were studied in four terms from May to July. The variability of 38 phenological, morphological and important agronomic characters was analyzed. The variation in plant characters and its dependence on the cultivar, year conditions, and different sowing dates were studied.Results and conclusion. As a result, crop cultivation practices for obtaining vegetable products in the southern regions of Russia were developed. A series of cowpea cultivars with different growing seasons was selected; some of them may be sown at different times in the period from early May to mid-July. Genotypes with high pod productivity were identified within different maturity groups. They are suitable for cultivation on spring and postharvest fields and capable of ensuring uninterrupted supplies of vegetable products to food processing enterprises.